Language maintenance among minority groups in Malaysia: a bibliometric analysis - Zuhaimi, Natasha; Rostam Affendi, Faiza; Yaacob, Zuriani; Tengku Paris, Tengku Nazatul Shima; Samsuri, Maimanah (GADING Journal for the Social Sciences, 2024)
The academic field of language maintenance refers to the study of approaches used to preserve minority languages. Malaysia is a multicultural nation comprising various ethnic groups that utilise distinct languages. The Malaysian language serves as the national language, while English is the widely utilised second language; however, some minority groups continue to maintain their heritage languages. The issue of language maintenance is discussed in a variety of research studies that fall under the umbrella of sociolinguistics. This study aims to investigate the scientific output on language maintenance through a bibliometric analysis of Scopus-indexed papers. There are a total of 781 scholarly papers included in the selected sample. The data that were produced from bibliometric analysis reveal that there has been a steady rise in publishing, journals of publication, the organisations and nations that have the greatest publication rates, and the works that are referred to the most frequently. Although language maintenance is now a physical reality, our study reveals that there is still room for improvement in terms of the quality of publications.